Emirical Analaysis of Solow-Swan Growth Model (Yearbook - Faculty of Economics, 2013)
Long-term rate of economic growth in the Solow-Swan model is determined by exogenous (previously given) variables, and as a result, in the model, percapita variables k, c and y grow only to a point where the economy reaches the steady-state level. From this we can conclude that the Solow-Swan model provides an opportunity to grow the economy, but in the long run. To explain this fact we will use one example. Suppose that the economy is in a state where capital per worker k is below the value in the steady-state condition, in which case capital and output per worker will grow, but only along the transition path to steady-state. On the other hand, when the goods on physical capital per worker exceeds the value of capital per worker in steadystate condition, then the economy has seen a decline in capital and output per worker along the transition path to steady-state level.